Kajian Potensi Lanskap Kota Medan untuk Pengembangan Wisata Sejarah - Fariz Harindra Syam; Nurhayati Arifin; Hadi Susilo Arifin (http://arl.faperta.ipb.ac.id/, 2019)
Medan is capital city of North Sumatera that established since 1590. Medan City has six historical area which there are many historical objects and landscapes. The six historical area are Kesawan, Maimun Palace, Polonia, Kampung Madras, Pulo Brayan, and Labuhan Deli Old City. The objectives of this study are to produce historical landscapes distribution map and to assess potential of historical tourism in the six historical area. This study used old map of Medan City (year 1913 and 1945) in order to assess for the distribution of historical objects/landscapes that still exist. The value of potential historical tourism obtained from total of authenticity, uniqueness, and tourism supporting factors. The results of the study show that Kesawan area has the most amount of historical objects/landscapes (19) with character of Netherland-Indische Colonial and China Town. Kesawan area also has the highest value of potential historical tourism. Besides that, Maimun Palace area and Polonia area also has high value of authenticity and uniqueness. Maimun Palace has strong character of Melayu Deli Sultanate and Polonia has strong character of Colonial. Location of this two areas are also adjacent with Kesawan area. Therefore, the Maimun Palace and Polonia area has high potential to be developed as historical tourism area.